2006
DOI: 10.2113/gsmicropal.52.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Pleistocene extinction of bathyal benthic foraminifera in the Caribbean Sea

Abstract: During the mid-Pleistocene Transition (MPT), 2 families, 14 genera and 41 species of benthic foraminifera (Extinction Group) declined in abundance (8-12 % of early Pleistocene benthic foraminiferal fauna) and finally disappeared at mid-bathyal depths in the Caribbean Sea (ODP Site 1000A, 916m depth), as part of the global extinction of at least 73 deep-water species at this time. At this site, the final phase of pulsed glacial decline, partial interglacial recoveries (0.8-0.67 Ma), and final extinction (0.58 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 71 publications
(104 reference statements)
1
41
0
Order By: Relevance
“…The majority of significant declines at each site occurred during glacial intervals and were interspersed with interglacial recoveries (Figures 4 and 5) [Hayward, 2002;Kawagata et al, 2005Kawagata et al, , 2006Kawagata et al, , 2007Hayward et al, 2006;O'Neill et al, 2007]. This pattern was most prominent at intermediate depths during the MPT, with marked declines at various sites between marine isotope stages MIS 24 and 16 (0.92-0.65 Ma).…”
Section: Pulsed Declines In Abundance and Diversitymentioning
confidence: 87%
See 3 more Smart Citations
“…The majority of significant declines at each site occurred during glacial intervals and were interspersed with interglacial recoveries (Figures 4 and 5) [Hayward, 2002;Kawagata et al, 2005Kawagata et al, , 2006Kawagata et al, , 2007Hayward et al, 2006;O'Neill et al, 2007]. This pattern was most prominent at intermediate depths during the MPT, with marked declines at various sites between marine isotope stages MIS 24 and 16 (0.92-0.65 Ma).…”
Section: Pulsed Declines In Abundance and Diversitymentioning
confidence: 87%
“…[4] The youngest interval has only recently been identified [Lutze, 1979;Weinholz and Lutze, 1989;Schönfeld, 1996], but our studies indicate that it was the most significant of the three younger species turnovers with 20 -25% of deep-sea foraminiferal diversity disappearing, mostly during the mid-Pleistocene Climate Transition (MPT, 1.2-0.55 Ma) [Hayward, 2001[Hayward, , 2002Kawagata et al, 2005Kawagata et al, , 2006Hayward et al, 2006;O'Neill et al, 2007]. The Eocene-Oligocene and mid-Miocene turnovers were more significant in turns of community structure but are reported to have resulted in fewer species originations or extinctions [Thomas, 1986a[Thomas, , 1986b[Thomas, , 1987.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Gooday and Jorissen (2012) found that deeper-water benthic foraminifer have broad geographic ranges that are controlled more by the amount of organic matter they receive. Studies have examined the effects of a widespread, mid-Pleistocene extinction of benthic foraminifera in the Caribbean at mid-bathyal depths (Hayward, et al, , 2006.…”
Section: Chapter 1 -Introductionmentioning
confidence: 99%